Energy Management: A Case Study on the Malaysian Government Office Building - Mohd Nawi, Mohd Nasrun; Baharum, Faizal; Rajemi, Mohamad Farizal; Ibrahim, Jafni Azhan; Tahir, Mohamad Zamhari (Research India Publications, 2014)
Based on the current needs of the sustainable and green technology in Malaysian construction industry, this research is led to look for and distinguish chances to better oversee energy use including the procedure of comprehend when, where, and how energy is utilized in a building. The motivation behind this research is to give a best practice rule as a pragmatic instrument to help construction industry in Malaysia to enhance the energy efficiency of the workplace building during the post construction by auditing the current practice of the building operation and maintenance in order to optimize the usage and reduce the amount of energy input into the building. Accordingly, this paper will review the current issue in energy management, and to investigate the energy flow in a building and also its energy dynamics. There were a few courses of action included and concentrated on specialized systems, for example, energy metering, tracing, harvesting, and auditing based on the case study. A Government office building in Putrajaya was chosen as a proper detailed analysis for this research. Toward the end of this exploration, it will suggest a vital approach or model in a particular rule for empowering energy efficient operation and maintenance in the office building